1986
DOI: 10.1021/j100280a066
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant dynamics in spherical and nonspherical micelles. A nuclear magnetic resonance study

Abstract: Decylammonium chloride dissolved in water at concentrations of 0.5 and 2.0 M has been studied by multifield carbon-13 and deuterium nuclear magnetic relaxation. Carbon-13 longitudinal relaxation times , and nuclear Overhauser effects have been obtained for all carbons in the aliphatic chain, at frequencies ranging from 15 to 90 MHz. Decylammonium chloride has been selectively deuterated at the a position with respect to the polar head. 2H longitudinal relaxation times T[ and, in some instances, transverse rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 0 publications
2
70
1
1
Order By: Relevance
“…NMR relaxation data suggest a higher degree of order near the surface than in the interior of the micelle. 42,43 So the high values of the order parameters are also a supportive indication of the fact that the probe molecules are located in the micelle-water interfacial region rather than the interior of the micelles.…”
Section: Time Resolved Fluorescence Anisotropymentioning
confidence: 97%
See 1 more Smart Citation
“…NMR relaxation data suggest a higher degree of order near the surface than in the interior of the micelle. 42,43 So the high values of the order parameters are also a supportive indication of the fact that the probe molecules are located in the micelle-water interfacial region rather than the interior of the micelles.…”
Section: Time Resolved Fluorescence Anisotropymentioning
confidence: 97%
“…Based on the NMR relaxation data, the lateral diffusion of the surfactant molecules under study in micelles are reported to be in the range of ͑0.2-1.5͒ ϫ 10 −6 cm 2 s −1 . 42,43 Thus it is important to note that the lateral diffusion of the AODIQ is faster than that of the surfactant molecules in these micelles. The order parameter of the probe in water is zero because the dye molecule tumbles freely and the distribution is completely random.…”
Section: Time Resolved Fluorescence Anisotropymentioning
confidence: 99%
“…The organization and dynamics of micellar environments, namely, the core, the interface, and the immediate layers of water on the interface, have been investigated using experimental (Shinitzky et al, 1971;Kalyanasundaram and Thomas, 1977;Mukerjee and Cardinal, 1978;Leung and Shah, 1986;Nery et al, 1986;Maiti et al, 1995;Saroja and Samanta, 1995) and theoretical (Gruen, 1985) approaches. It is fairly well established that practically all types of molecules have a surface-seeking tendency in micelles (due to very large surface area to volume ratio) and that the interfacial region is the preferred site for solubilization, even for hydrophobic molecules (Mukerjee and Cardinal, 1978;Ganesh et al, 1982;Shobha and Balasubramanian, 1986;Shobha et al, 1989).…”
Section: Wavelength-selective Fluorescence In Micellesmentioning
confidence: 99%
“…Lateral diffusion of the donor and acceptor molecules over the micelle surface is included and expected to be significant. 1,7,[14][15][16] Since each micelle will have a different configuration of acceptor/donors distributed over the surface, calculation of the observed electron-transfer dynamics requires performing the ensemble average with the lateral diffusion of the molecules appropriately included. Details of the theory were given in ref 1.…”
Section: Model and Theorymentioning
confidence: 99%